Persepsi Siswa Terhadap Pembelajaran Daring pada Masa Pandemi pada Tahun Ajaran 2020/2021 - Destel Meri; Rima Agreini (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2021)
ABSTRACT The purpose of the study was to determine students' perceptions of online learning that had been implemented in the 2020/2021 school year. The research method used is qualitative research. The results showed: 1) Based on the questionnaire, 80% of students answered that they were not interested in online learning, students gave reasons including not having an android, the network was not smooth, and unable to buy internet quota. As well as by reason of difficulties in understanding lessons and boredom in carrying out learning activities at home. The conclusion of the study is that 8 out of 10 students are not interested in online learning. Then based on the results of teacher interviews, the difficulties experienced in the online learning process are also very diverse, including not all students have androids, the teacher's ability about online learning application technology is still relatively new, the media used is not varied. Keywords: Online Learning, Pandemic, Perception